(untitled) (Comprehensive Journal of Science, 2025)
Background: Breast cancer is the most common malignancy among women in Libya and is frequently diagnosed an advanced stage, adversely affecting prognosis and survival. Evidence on factors independently associated with late-stage presentation in Libya remains limited, particularly from studies employing multivariate statistical methods. Objectives: This study aimed to identify the demographic, reproductive, behavioral, and biological factors independently associated with advanced-stage breast cancer diagnosis (Stage III) among Libyan women. Methods: An analytical cross-sectional study was conducted among 220 women with histologically confirmed breast cancer treated at the Al-Riaya Medical Clinic, Tripoli. Data were obtained from structured interviews, medical records, and laboratory databases covering the period 2017–2022. The outcome variable was stage at diagnosis, dichotomized into early stage (Stages I–II) versus advanced stage (Stage III). Multivariate logistic regression analysis was performed to estimate adjusted odds ratios (AORs) and 95% confidence intervals (CIs) for factors associated with Stage III diagnosis. Results: Of the 220 patients, 44% were diagnosed at Stage III. After adjustment for potential confounders, nulliparity was the strongest predictor of advanced-stage diagnosis (AOR = 6.42, 95% CI: 2.87–14.36; p < 0.001). Symptom-based detection was associated with nearly a fivefold increased likelihood of Stage III disease compared with screening-based diagnosis (AOR = 4.91, 95% CI: 2.24–10.77; p < 0.001). Physical inactivity (AOR = 3.15, 95% CI: 1.45–6.84; p = 0.004), positive family history of cancer (AOR = 2.78, 95% CI: 1.33–5.82; p = 0.007), and vitamin D deficiency (AOR = 2.21, 95% CI: 1.12–4.35; p = 0.022) were also independently associated with advanced-stage diagnosis. Elevated fasting blood glucose showed a positive but non-significant association with Stage III disease.